Mediterranean oak woodland working landscapes : Dehesas of Spain and Ranchlands of California - Huntsinger, Lynn; Oviedo Pro, Jose Luis; Starrs, Paul F.; Diaz, Mario; Standiford, Richard B.; Montero, Gregorio; Campos, Pablo (Landscape Series, 2013)
The oak tree was a boon companion as humans expanded their presence across much of the globe. While oak woodlands (Quercus spp.) come today in stunningly diverse forms, the stately dehesas of Spain and the dramatic oak-dominated ranchlands of California are working landscapes where cultivation and manipulation for a couple of millennia have shaped Mediterranean-type ecosystems into a profoundly modified yet productive environment that is sought-after by every manner of species. The grazing of wildlife and livestock in oak woodlands yields a remarkable plant and animal biodiversity, creating a mosaic of habitats and visually pleasing savannas. Added products unique to Spain such as Iberian pigs and cork, and in California multiple landowner benefits, include valued ecosystem services that allow owners, visitors, and conservation supporters to experience the benefits of woodland life. With its 15 chapters a decade in the making, this handsomely illustrated book covers key topics in oak woodland policy, ecology, and management in Spain and California, presenting new research results and reviewing an existing expert literature.